Aplikasi Model Optimasi untuk Meningkatkan Efisiensi Pengangkutan Sampah di Kota Cilegon - Triwibowo, Danang; Halimatussadiah, Alin (Jurnal Ekonomi dan Pembangunan Indonesia, 2015)
Most cities in developing countries face inefficiency problem of waste collection service run by government. The purpose of this study is to estimate the efficiency of waste collection service and the capital cost requirement in 2019 to cover 100% waste collection service in Cilegon City. The efficiency is calculated by comparing the current costs with the optimization costs by the model of vehicle routing problem. The result shows that the obtained inefficiency reaches 37,48% which largely comes from the labor component. To cover all of resident in Cilegon City, the city needs to increase their budget allocation as much as IDR 33,884 billion in 2019.